Transport Ratios of the Kinetic Alfvén Mode in Space Plasmas - Narita, Yasuhito; Roberts, Owen Wyn; Vörös, Zoltán; Hoshino, Masahiro (Frontiers in Physics, 2020)
Fluctuation properties of the kinetic Alfvén mode such as polarization of the wave electric and magnetic field around the mean magnetic field, parallel fluctuation to the mean field, ratios of the electric to magnetic field, and density fluctuations are analytically estimated by constructing the dielectric tensor of plasma based on the linear Vlasov theory. The dielectric tensor contains various fluid-picture processes in the lowest order, including polarization drift, Hall current, and diamagnetic current. Major discoveries from the dielectric tensor method in the kinetic Alfvén mode study are (1) identification of the mechanism of the field rotation sense reversal as a result of competition between the Hall and diamagnetic currents, (2) asymptotic behavior of the parallel magnetic field fluctuation (in the compressive sense). The analytic expression of transport ratios serves as a diagnostic tool to study and identify the kinetic Alfvén mode in space plasma observations in the inner heliospheric domain.